Patients with dermatomyositis shared partially similar transcriptome signature with COVID-19 infection - Yiying Yang; Jie Song; Hongjun Zhao; Huali Zhang; Muyao Guo (Autoimmunity, 2023)
Dermatomyositis (DM) is an autoimmune disease that primarily affects the skin and skeletal muscle. Virus infection and type I interferon-related signaling pathways play an important role in the pathogenesis of dermatomyositis. In this study, we found that the skin of patients with DM and the skin of patients with COVID-19 have similar transcriptional profiles, and identified key genes involved in dermatomyositis based on bioinformatics analysis. These hub-genes might be served as potential biomarkers for the early diagnosis and therapy of DM, including MX1, ISG15, IFIT3, IFIT1, RSAD2, IFIT2, IFI6, XAF1, IRF9, MX2.